The Impact of Shipping Costs and Advertising on Shopee Buying Interest from Shopee in Students of Economic Education Study Universitas HKBP Nommensen Pematangsiantar Year 2019 - Jumiati Silalahi (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the effect of free shipping and advertising on buying interest from Shopee among students of the 2019 Stambuk economics education study program at HKBP Nommensen Pematangsiantar University. The variables in this research are free shipping and advertising as the independent variable and purchase interest as the dependent variable. This type of research is quantitative research with a survey data analysis approach, with the research population being all students from group A and B of the 2019 Stambuk Economics Education Study Program at HKBP Nommensen Pematang Siantar University and the sample for this research is group B students, totaling 60 students. Data collection techniques use instruments: (1) free postage questionnaire, (2) advertising, and (3) purchase interest. The results of this research show that: (1) there is a positive and significant influence of free shipping on purchase interest, this result can be seen in the t test where the calculated t value > t table (3.223 > 1.6715) (sig.) < 0.05 as much as 0 Free Shipping and Advertising on buying interest from shopee 025, then it is significant. (2) there is a positive and significant influence of advertising on buying interest, this result can be seen in the t test where the t-count value > t-table (2.407 > 1.6715) with (sig.) < 0.05, namely 0.05, then significant. (3) Free shipping and advertising together influence purchasing interest, this result can be seen in the F test where the F-calculated value is higher than the F-table ( 5.738 > 3.15 ) and the significance is lower than 0.05 ( 0.000 < 0.05). The R Square coefficient of determination test is known to be 0.138, which means that 13.8% of the free shipping and advertising variables influence the buying interest of students in the 2019 Stambuk Economics Education Study Program, HKBP Nommensen University, Pematang Siantar and the remaining 86.2% is the influence of other variables not examined in this research.